2016
DOI: 10.1136/archdischild-2015-309396
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions in neonates: a prospective study

Abstract: There is a high incidence of ADRs in hospitalised newborns, which increases with the number of prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
5
18
1
1
Order By: Relevance
“…The most commons ADRs linked to systemic antibiotics were digestive for older children, while hematologic were for neonates. Similar findings were reported by Belen-Rivas et al [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most commons ADRs linked to systemic antibiotics were digestive for older children, while hematologic were for neonates. Similar findings were reported by Belen-Rivas et al [19].…”
Section: Discussionsupporting
confidence: 92%
“…These results differ with the findings of Shamna et al [39], who found that moderate ADRs were the most common. According with Naranjo's algorithm, the majority of ADRs were classified as probable; also Belen-Rivas [19] reported that the majority of ADRs were probable. The evaluation of ADRs is predisposed by the definitions, the methodology of detection, classification, and the study setting included.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, dado que el período de observación fue de seis meses, el estudio permitió determinar la incidencia y el comportamiento de las reacciones adversas en los pacientes estudiados, y se encontraron datos similares a los reportados en otros estudios (22,24,26).…”
Section: Factores De Riesgo Asociados a La Aparición De Las Reaccioneunclassified
“…However, these reports did not specify the frequency of ADRs in children under 6 years of age and seemed to show underestimated rates, as other studies have reported higher incidences 10 . In addition, younger ages (children from 1 month to 2 years old), male sex, prolonged and previous hospitalization, indication of antibiotics and a higher number of prescribed drugs are factors associated with a higher risk of ADRs 10 , 11 . In the case of Colombia, no specific data about ADRs frequency and characteristics has been described for this population, which is considered a priority in the sustainable development goals.…”
Section: Introductionmentioning
confidence: 99%